A Bibliometric Analysis of The Relationship Between Influence and E-Commerce - Muh. Nasar; Achmad Riyadi; Fadly Yashari Soumena (www.amertainstitute.com, 2024)
The rapid growth of e-commerce has reshaped consumer shopping behaviors, offering greater access to products, prices, and reviews. Influencers have emerged as pivotal players in e-commerce marketing by leveraging their digital platforms to shape consumer perceptions and behaviors. This research employs bibliometric analysis to examine the relationship between influencers and e-commerce, focusing on trends, patterns, and the effectiveness of various influencer characteristics. Data was sourced from the Dimensions database and analyzed using VOSviewer software to visualize keyword networks and research collaborations. The findings highlight the dominance of Chinese institutions and publications in this field, underscoring their influence on global academic discourse. The analysis also reveals critical gaps, particularly in the examination of influencer strategies on long-term customer loyalty and satisfaction within emerging markets. By addressing these gaps, this study contributes to a deeper understanding of how influencers can optimize e-commerce campaigns, offering valuable insights for scholars and practitioners in digital marketing. The study emphasizes the need for interdisciplinary collaboration and further exploration of the intersection between influencer marketing and consumer behavior.